6 - The Relationship Between Vice-Chancellors’ Leadership Behaviour and the Work Behaviour of Lecturers in Nigerian Universities: Implication for Leadership Training for Vice-Chancellors - Ganiyu G. Oke,; P.O. Okunola,; Adesoji A. Oni,; J.A. Adetoro, (Journal of Higher Education in Africa, 2010)
The study examined the relationship between the leadership behaviour of Vice-Chancellors and the work behaviour of lecturers in the universities of South-West Nigeria. The study employed the correlational research design. Twelve out of the 27 universities in the South-West geo-political zone were selected as the study sample, using the stratified sampling technique. Two sets of questionnaires were adapted and used for data collection. The in- struments contain items relating to the leadership behaviour of Vice-Chan- cellors and the work behaviour of lecturers. The second was measured in terms of level of participation in university administration, cooperation, com- mitment and conformity. Lecturers’ perception of the influence of Vice-Chan- cellors’ leadership behaviour on their work behaviour was assessed on a rating scale ranging from 1 to 4. Four null hypotheses were posited and tested using the Pearson Product Moment Correlation. The test revealed varying degrees of association between Vice-Chancellors’ leadership behaviour and lecturers’ work behaviour. Recommendations for enhancing the effectiveness and efficiency of the university system aimed at the development of a culture of high level cooperation, commitment, participation and conformity of lecturers included a proposed leadership training programme for Vice-Chancellors. To facilitate the proposed training programme, sensi- tivity training, T-groups, in-baskets, case studies, business games behaviour modelling and action learning techniques are particularly recommended